Analisa Perencanaan Dan Pengendalian Persediaan Bahan Baku Pada Home Industry Di Batam - Wibowo, Sadiq Ardo; Citra Indah Asmarawati; Susanti, Elva (Metode : Jurnal Teknik Industri, 2023)
Inventory refers to goods owned by the company within a certain period of time, which are used to facilitate production and meet consumer demand. Inventory can be in the form of raw materials, work in progress, and finished goods. This study aims to analyze the planning and inventory control of raw materials in home industries in Batam. Efficiency and effectiveness of raw material supplies are critical to the successful operation of a cottage industry. One problem that often occurs is the accumulation of raw material inventories which can cause an increase in inventory costs. This study uses descriptive and quantitative analysis methods by collecting data from several cottage industries in Batam. The methods used in this research include economic order quantity (EOQ), reorder point (ROP), safety stock, and maximum stock. Through calculations, the EOQ value for house materials is 602.35 units, while for tumblers it is 644.76 units.